PENGKAJIAN VIABILITAS BENIH DENGAN TETRAZOLIUM TEST PADA JAGUNG DAN KEDELAI - Renan Subantoro; Rossi Prabowo (Universitas Wahid Hasyim, 2013)
Tetrazolium test is a test of dehydrogenase enzyme activity in seed tissue, so that the tissue is known to live or die in the embryo. The basic principle of this test is used chemical reduction of tetrazolium chloride 3,3,5 Triphenil initially colorless be red tissue. Staining intensity indicates the viability of the tissue. Tissue on seed dies, certainly not able to germinate seeds or germinated abnormally. This experiment using corn seed (monocots) and soybean seed (dicots). Testing seed viability quickand topography using tetrazolium salt solution and to control seed viability testing with germinated in germination plate. Both of these tests using a t-test. The results of the study are: corn seed viability testing quick by using the tetrazolium test can be conducted show significantly different results with the results of direct germination test (control), environmental factors on the test field with sand media should be controlled so that the optimum for germination, and seed are still viable indicated by a color change in the embryo and endosperm become red. . Key Words : Tetrazolium, Viability, Enzim Dehidrigenase, Seed